Mapping Research on mHealth and Wearable Technologies in Sports and Gaming: A Bibliometric and Visualization Approach (2005– 2025) - Panackal, Martin Babu; Mathew, Praseedha; Sunny, Sandeep; Joseph, Jeena; Jose, Jobin (Informatica, 2025)
Recent years have seen a surge in the development of wearable health technologies for real-time monitoring, personalized intervention, and gamification in sports and healthcare. However, research in this domain remains fragmented across themes and applications. This study presents a bibliometric overview of research trends, collaboration patterns, and emergent themes in mHealth and wearable technologies within sports and gaming literature from 2005 to 2025. Using bibliometric analysis, we extracted data from the Scopus database, selecting 793 documents from 455 sources based on the keywords “sports” OR “games” AND “wearable health” OR “mHealth.” The PRISMA methodology was used for refining the dataset to include only articles, book chapters, and conference papers. To analyze research trends, co-authorship networks, and keyword co-occurrence patterns, we employed VOSviewer, CiteSpace, and Biblioshiny. The results indicate an annual growth rate of 7.18%, with research peaking in 2023. Collaboration analysis reveals an international co-authorship rate of 21.19%, with an average of 4.77 authors per publication. The keyword co-occurrence network highlights "mHealth," "wearable sensors," "gamification," and "artificial intelligence" as dominant research themes, with mental health interventions and cognitive training emerging as new areas of focus. The study also identifies Hlavacs H. and Jiang Y. as the most influential authors and JMIR mHealth and uHealth as the most prolific journal with 31 publications in this domain. These findings underscore the interdisciplinary and collaborative nature of research in mHealth and wearable technologies for sports and gaming. Future research should focus on AI integration, equitable access, and long-term impact assessments to fully leverage the potential of these technologies in enhancing health outcomes and sports performance.